2018
DOI: 10.1021/acsomega.8b02134
|View full text |Cite
|
Sign up to set email alerts
|

Novel “Turn-On” Fluorescent Probe for Highly Selectively Sensing Fluoride in Aqueous Solution Based on Tb3+-Functionalized Metal–Organic Frameworks

Abstract: A Zr-based metal–organic framework (Zr-MOF) which has free carbonyl groups is synthesized successfully through mix-ligand strategy. Subsequently, Tb 3+ is encapsulated into a Zr-MOF by postcoordinated modification. The Tb 3+ @Zr-MOF exhibits the characteristic emission of Tb 3+ because of efficient sensitization through antenna effects. The Tb 3+ @Zr-MOF is further developed as a novel “turn-on” fluorescent probe to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Compared to instrumental analysis, such as ion chromatography, inductively coupled plasma‐mass spectrometry, fiber optic wave sensors, coupled with atomic absorption spectrometry,chemical methods including fluorescent and colorimetric methods, typically take shorter processing time and less sample pretreatment works . Moreover, luminescent coordination polymers (CPs) have been widely studied as chemical sensors owing to their significant advantages, namely, high selectivity, high sensibility, short response time, easy to operate and visualization …”
Section: Introductionmentioning
confidence: 99%
“…Compared to instrumental analysis, such as ion chromatography, inductively coupled plasma‐mass spectrometry, fiber optic wave sensors, coupled with atomic absorption spectrometry,chemical methods including fluorescent and colorimetric methods, typically take shorter processing time and less sample pretreatment works . Moreover, luminescent coordination polymers (CPs) have been widely studied as chemical sensors owing to their significant advantages, namely, high selectivity, high sensibility, short response time, easy to operate and visualization …”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have emerged as a class of promising and unique materials owing to their high porosity and large surface area. , MOFs have shown potential applications in the fields of gas storage, , separation, , sensors, drug delivery, , catalysis, and biomimetics. Especially, lanthanide MOFs (Ln-MOFs), formed by coordination of lanthanide metal ions to organic ligands, are generally preferred to construct skeletal materials having luminescent properties. Luminescent Ln-MOFs exhibit unique fluorescent properties, such as large Stokes shifts, long fluorescence lifetime, narrow emission spectra, etc. On the basis of these unique advantages, Ln-MOFs have drawn great attention for sensing applications. It has been previously reported that MOFs functionalized by NH 2 or SH groups are high-efficiency probes for Hg 2+ detection due to the interaction between Hg 2+ ions and N, S. However, these methods are based on the coordination of Hg 2+ to amino or thiol groups, and other metal ions having similar electronic shell structures can influence detection . Most importantly, although CH 3 Hg + showed much more toxicity than Hg 2+ , few probes have been reported for the detection of CH 3 Hg + , especially the simultaneous detection of Hg 2+ and CH 3 Hg + .…”
mentioning
confidence: 99%
“…In the past decades, numerous fluorescent probes have been developed for fluoride based on different fluoride-participated processes, such as fluoride-induced Si−O or Si−C bond cleavage, H−F hydrogen bonding formation, and Lewis acid−base interactions [136,137,138]. By exploiting these special reactivities of fluoride, several MOF-based luminesscent probes have recently been developed for its detection [139,140].…”
Section: Mof-based Chemodosimeters For Ionsmentioning
confidence: 99%